In vitro digestibility and proteases inhibitory effect of several feedstuffs for Parachromis dovii juveniles and P. dovii hybrid larvae - Valverde-Chavarría, Silvia (2016)
Parachromis dovii, a native cichlid from Costa Rica, is highly appreciated for its size and flesh quality. Further, P. dovii easily accept inert feed from the beginning of exogenous feeding; however, its growth is low compared to live food. For this reason, evaluation of several feedstuffs using two in vitro techniques was done. The quantification of the in vitro inhibitory effect of seven plant ingredients on the alkaline protease activity was done using enzymatic extracts from larvae samples of 6, 15, 22 and 30 days after hatching (DAH). The in vitro alkaline digestibility assays were run for six protein sources (from animal and plant origin) using the enzymatic extract from larvae 30 DAH. Independent of fish age, all plant feedstuffs reduced alkaline digestive proteases activity; however, the wheat flour (14.1 % at 6 DAH, 33.4 % at 15 DAH) and broken rice meal (51.6 % at 22 DAH) showed the lowest inhibition percentage of alkaline digestive activity, whereas the highest inhibition percentage was found with soybean and palm kernel meals (92.5 % at 30 DAH and 87.4 %, respectively) (P < 0.05). The alkaline proteases inhibition percentage of feedstuffs varied during larvae ontogeny. From six protein dietary sources tested, tankage and fish meal presented the highest in vitro digestibility values, 113.9 and 74.9 %, respectively. Contrary, the lowest digestibility was found for blood and soybean meals (38.07 and 19.82 %, respectively).